A comparison of the developmental experiences of elite and sub-elite swimmers: similar developmental histories can lead to differences in performance level - Johnson, M. B.; Tenenbaum, G.; Edmonds, W. A.; Castillo, Y. (Sport, Education and Society, 2008)
The current study fills a void in the literature that investigates the factors required for elite athlete development. Previous studies have (a) illustrated psychological and physiological differences between elites and non-elites; or (b) described the psychological and physiological developmental experiences of elite performers. The current study augments these research bases by obtaining the recollections of 15 highly accomplished swimmers (i.e. seven elite and eight sub-elite) and compares their developmental experiences. Qualitative results are presented within Bloom's (1985) stages of talent development (i.e. The Early, Middle and Late Years) and Hendry and Kloep's (2002) lifespan model of developmental challenges (i.e. Self-Efficacy, Social Resources, Structural Resources, Skills and Biological Dispositions) in order to present these athletes` idiosyncratic experiences in an organised manner. Similarities and differences among these athletes and between performance groups are presented, some of which are incongruent with current theories that address the developmental requirements of elite athletes. A discussion regarding the implications of these findings, and future research concerns, are then proffered.